Postpartum psychiatric readmissions: A nationwide study in women with and without epilepsy. (10th March 2021) - Isseroff, Devora; Lin, Jung‐Yi; Kwon, Churl‐Su; Agarwal, Parul; Mazumdar, Madhu; Dhamoon, Mandip; Howell, Elizabeth A.; Jetté, Nathalie
Abstract: Objective: To assess whether epilepsy is associated with increased odds of 30‐day readmission due to psychiatric illness during the postpartum period. Methods: The 2014 Nationwide Readmissions Database and the International Classification of Disease, Ninth Revision, Clinical Modification codes were used to identify postpartum women up to 50 years old in the United States, including the subgroup with epilepsy. The primary outcome was 30‐day readmission and was categorized as (1) readmission due to psychiatric illness, (2) readmission due to all other causes, or (3) no readmission. Secondary outcome was diagnosis at readmission. The association of the primary outcome and presence of epilepsy was examined using multinomial logistic regression. Results: Of 1 558 875 women with admissions for delivery identified, 6745 (.45%) had epilepsy. Thirteen of every 10 000 women had 30‐day psychiatric readmissions in the epilepsy group compared to one of every 10 000 in the no‐epilepsy group ( p  < .0001). Of every 10 000 women with epilepsy, 256 had 30‐day readmissions due to other causes compared to 115 of every 10 000 women in the no‐epilepsy group ( p  < .0001). The odds ratio for readmission due to psychiatric illness was 10.13 (95% confidence interval = 5.48–18.72) in those with epilepsy compared to those without. Top psychiatric causes for 30‐day readmissions among women with epilepsy were mood disorders, schizophrenia and other psychotic disorders, and substance‐related disorders. Significance: This large‐scale study demonstrated that postpartum women with epilepsy have higher odds of readmission due to a psychiatric illness compared to women without epilepsy. Postpartum treatment strategies and interventions to prevent psychiatric readmissions are necessary in this vulnerable population.